Flood loss functions as decision support for guiding resilient urban development: a case study of Gaur Municipality, Nepal - Kafle, Tanka Prasad; Kafle, Anup; Hazarika, Manzul Kumar (Journal of Engineering Issues and Solutions, 2024)
Flood loss functions convert damage and loss of function into economic losses, providing critical information on expected damages from future floods. This article presents the outcomes of a study assessing the economic impacts of an extreme flood event in Gaur Municipality, Nepal, utilizing flood simulation results from a hydrodynamic model. A detailed questionnaire survey was conducted covering all parts of the municipality to collect data to assess the economic impacts of flooding on different types of buildings (e.g., adobe, masonry, and RCC frame) and agricultural lands. Subsequent statistical analysis considering building plinth height, number of stories, building age, etc., showed flood depth and duration to be the most sensitive parameters for the damage. Sets of linear and logarithmic depth-damage functions were generated and compared to predict damages for different buildings and crops. The study revealed a significant economic burden on the municipality from potential extreme floods, with estimated structural damage to residential and commercial buildings reaching NRs—225 million (US 3.21 million). This figure is expected to rise with time due to urbanisation growth and subsequent wealth accumulation within the municipality area. The developed flood damage functions predict damages, while the flood loss map, highlighting regional vulnerability, aids in planning development activities within the municipality and provides economic justification for long-term investments in flood protection measures. This study is the first in Nepal to generate flood damage functions, paving the way for informed and resilient urban development.